Clinical efficacy and pharmacological mechanism of Er Zhi Tian Gui formula in enhancing IVF-ET outcomes for diminished ovarian reserve - Chen, Wen; Lian, Fang; Song, Jingyan; Yu, Chen; Ding, Shengyong; Wu, Haicui (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the efficacy of the Er Zhi Tian Gui Formula (EZTGF) in diminished ovarian reserve (DOR) patients undergoing in vitro fertilization-embryo transfer (IVF-ET); to examine the pharmacological mechanism of EZTGF in inhibiting ovarian granulosa cell (OGC) apoptosis.MethodsA total of 120 DOR patients undergoing IVF-ET in the Affiliated Hospital of Shandong University of TCM from March to December 2021 were randomly assigned to the EZTGF (n = 60) or Placebo (n = 60) groups. All participants followed a gonadotropin-releasing hormone antagonist protocol for controlled ovarian stimulation, with interventions starting on days 2–3 of the preceding menstrual cycle and continuing until the trigger day. IVF-ET outcomes measured included the number of oocytes retrieved, embryo quality, and pregnancy rates. NEAT1, miR-10b-3p, and FOXO3a OGCs expression was analyzed via qRT-PCR. Mechanistic studies were conducted using KGN cells, with dual-luciferase reporter assays confirming regulatory relationship between NEAT1, miR-10b-3p, and FOXO3a.ResultsA total of 116 patients completed the trial (58 in each group). The EZTGF group showed a significant increase in both the number (especially at the cleavage stage) and rate of high-quality embryos, compared with the Placebo group (P < 0.05). No statistically significant differences in pregnancy outcomes were observed (P > 0.05). Cellular experiments showed that miR-10b-3p inhibits proliferation and promotes apoptosis in oocyte granulosa cells (OGCs). Dual luciferase reporter gene assay confirms target-regulatory relationship of NEAT1 with miR-10b-3p, miR-10b-3p and FOXO3a. EZTGF treatment partially reversed the low expression of NEAT1 and FOXO3a, and the high expression of miR-10b-3p in OGCs from DOR patients.ConclusionTreatment with EZTGF enhances embryo quality in women with DOR undergoing IVF-ET, which can be partially attributed to modulation of the NEAT1/miR-10b-3p/FOXO3a pathway. Trial registration: ChiCTR2100052522.